RNA based viral silencing suppression in plant pararetroviruses - Hohn, Thomas (Frontiers in Plant Science, 2015)
The 600 nucleotide long leader of Cauliflower Mosaic Virus pregenomic RNA and that of other plant pararteroviruses is also separately transcribed. It is then converted to a double strand giving rise to a huge set of siRNAs, which suppress silencing.